Homeownership Intentions: The Influence Of Physical And Social Environment, Attitudinal Factors, Place Attachment, And Income Differentials - Hew, Wee Lim (2023)
Declining homeownership intentions is a problem that is escalating among middle and low-income group. While affordability is commonly assumed to be the reason for deferring homeownership tendencies, there are many other factors at play. Thus this research investigates the impact of residential environment, attitudinal factors on homeownership intentions through the mediation of place attachment and moderation of income differentials between the middle and lower-income groups. A framework was then devised based on the Mehrabian-Russell Model and complemented with the Theory of Planned Behaviour, and a survey on nonhomeowners in Selangor, Kuala Lumpur, Perak, Pulau Pinang, Johor, and Melaka was subsequently conducted between February to July 2020. Data was analysed using PLS-SEM. The research found that the social factors such as the residents' sociability and civility, as well as individuals' attitude towards homeownership. social influences, and perceptions of their future financial security, have significant impact on their attachment towards their place of residence, and this feeling drives their intention to own a home. The research also found both income groups to be indifferent in their perceptions and homeownership sentiments, except in their perceptions of future financial security. This research has several implications.